O uso do livro-texto na pedagogia da flauta transversal no Brasil: um estudo preliminar - Ariadne Araujo Paixao (2005)
The use of a textbook in flute teaching is of fundamental importance as a pedagogical guide for both, teachers and students. The textbook allows information, reflection and analysis on several issues that belongs to flute learning and practicing process. Considering these aspects, the present work consists on a study on the use, by teachers and professors, of the textbook for flute teaching in Brazil. Therefore, primarily it was made a study on the situation of flute teaching in the academic environment. This was accomplished trough a survey by distributing questionnaires to teachers and professors from different institutions. Secondly an analysis on the collected data was done. The result of this investigation revealed characteristics and problems concerning the employment of flute textbook around Brazil. A dramatic fact to be pointed in the outcome of the field research is that many of interviewed teachers were ignorant about any sort of didactic publication in the area. Added to that, it was detected that difficulties related to access a specialized published data, and the lack of material in Portuguese language, were among the main obstacles that justified the absence of a textbook for flute teaching. Finally, this work permitted a general view on the textbooks that already exist and have been available to be accessed by flute teachers and professors in Brazil. And fortunately these publications cover a broad range of content and method.